Peran Orang Tua dalam Mempengaruhi Hasil Belajar Maksimal Anak Jenjang SMA - Soedjono Soedjono (Journal of Physical Activity and Sports (JPAS), 2020)
Student learning outcomes are one indicator of the success of educators in carrying out the teaching and learning process. The purpose of the study was to describe the role of parents in instilling discipline so as to improve student learning outcomes.This research used descriptive qualitative approach. Data collection was conducted by in-depth interviews with informants, filling out check lists and field observations. The results of the study showed that parents played a role in instilling discipline. Discipline was implemented with full commitment, so that it could bea family culture. The obstacles of discipline implementation were the difference point of views between children and parents, but this can be solved by communication and deliberation. Therefore to improve discipline, parents needed to be assertive in children to carry out disciplined commitments, especially religious discipline, study, play, and help with homework. Having a commitment to carry out activities with discipline, learning outcomes can be achieved. Keywords: discipline, commitment, learning outcomes Abstrak Hasil belajar siswa merupakan salah satu indikator keberhasilan pendidik dalam melaksanakan proses belajar mengajar. Tujuan penelitian ini adalah untuk mendeskripsikan peran orang tua dalam menanamkan kedisiplinan sehingga dapat meningkatkan hasil belajar siswa. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Pengumpulan data dilakukan dengan wawancara mendalam dengan informan, pengisian check list dan observasi lapangan. Hasil penelitian menunjukkan bahwa orang tua berperan dalam menanamkan kedisiplinan. Disiplin dilaksanakan dengan penuh komitmen, sehingga bisa menjadi budaya keluarga. Hambatan dalam penerapan disiplin adalah perbedaan pandangan antara anak dan orang tua, namun hal ini dapat diselesaikan dengan komunikasi dan musyawarah. Oleh karena itu untuk meningkatkan kedisiplinan, orang tua perlu bersikap tegas pada anak untuk melaksanakan komitmen disiplin terutama disiplin agama, belajar, bermain, dan membantu pekerjaan rumah. Memiliki komitmen untuk melaksanakan kegiatan dengan disiplin maka hasil belajar dapat tercapai